2006
DOI: 10.1007/s11274-006-9161-1
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of the ability to decolorize dyes by laccase: relationship between redox mediators and laccase isoenzymes in Trametes versicolor

Abstract: The effect of redox mediators in the dye decolorization by two laccase isoenzymes from Trametes versicolor cultures supplemented with barley bran has been investigated. All the redox mediators tested, 1-hydroxybenzotriazole (HBT), promazine (PZ), para-hydroxybenzoic acid (pHBA) and 1-nitroso-2-naphthol-3,6-disulfonic acid (NNDS), led to higher dye decolorization than those obtained without mediator addition. Among the different tested mediators, PZ was the most effective one at a low range of concentration (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…A range of enzymes are synthesized during mushroom growth on these substrates including laccases [benzenediol:oxygen oxidoreductases (EC 1.10.3.2)], copper-containing enzymes that catalyze the oxidation of a broad spectrum of phenolic compounds and non-phenolic substrates using molecular oxygen as the electron acceptor. Laccases are widely distributed among fungi, where they have been assigned roles in lignin degradation (Bourbonnais et al 1995;Eggert et al 1997), in rendering phenolic compounds less toxic via oxidative coupling and polymerisation (Bollag et al 1988; Moldes and Sanroman 2006) and in mushroom fruit-body morphogenesis (Zhao and Kwan 1999;Chen et al 2004). Laccases may be either constitutive or inducible, and many factors including culture parameters (Fu et al 1997), heavy metals (Baldrian and Gabriel 2002;Chen et al 2003) and aromatic compounds (Scheel et al 2000) are reported to influence enzyme production in different fungal species.…”
Section: Introductionmentioning
confidence: 99%
“…A range of enzymes are synthesized during mushroom growth on these substrates including laccases [benzenediol:oxygen oxidoreductases (EC 1.10.3.2)], copper-containing enzymes that catalyze the oxidation of a broad spectrum of phenolic compounds and non-phenolic substrates using molecular oxygen as the electron acceptor. Laccases are widely distributed among fungi, where they have been assigned roles in lignin degradation (Bourbonnais et al 1995;Eggert et al 1997), in rendering phenolic compounds less toxic via oxidative coupling and polymerisation (Bollag et al 1988; Moldes and Sanroman 2006) and in mushroom fruit-body morphogenesis (Zhao and Kwan 1999;Chen et al 2004). Laccases may be either constitutive or inducible, and many factors including culture parameters (Fu et al 1997), heavy metals (Baldrian and Gabriel 2002;Chen et al 2003) and aromatic compounds (Scheel et al 2000) are reported to influence enzyme production in different fungal species.…”
Section: Introductionmentioning
confidence: 99%
“…Different compounds that could act as potential redox mediators need to be screened since the prediction about the behavior of a compound as a redox mediator is difficult because of different factors affecting the effectiveness of a mediator such as difference of redox potential between the enzyme and the mediator, the type of substituents in the mediator and their position, the properties of the oxidized form of the mediator such as stability, capability of inactivation of laccase, substrate affinity, concentration of the mediator used, etc. (Moldes and Sanroman 2006). Slower decolorization with HBT, SA, HQ and DMP than that obtained with the control flasks could be attributed to the inhibition of laccase because of the radicals generated in the process while the increase in absorbance with pyrogallol as the mediator could be because of the formation of colored oxidation products interfering with absorbance measurements (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The negative effect of some of the mediators on the stability of laccase has been reported. Moreover, in case of mediators such as HBT (at high concentrations), where the HBT radical is the real oxidizing agent, it is known that at high concentrations these radicals can attack some of the amino acids in the protein such as tyrosine and tryptophan, thus inactivating the enzyme (Moldes and Sanroman 2006). Thus, these results led us to the further use of ABTS-laccase system for the decolorization of different dyes using purified laccase from B. juncea hairy roots.…”
Section: Discussionmentioning
confidence: 99%
“…The mediators selected were 1-hydroxybenzotriazole (HBT), 4-hydroxybenzoic acid (HBA), 4-acetamido-TEMPO (TEMPO), syringaldehyde and acetosyringone (60 mM solution prepared with ethanol). Those compounds are typical laccase mediators used for dye decolourization [14,15,28]. The reaction mixture (300 l) contained 50 mM MES-glycine buVer (pH 9.0), dye (Wnal concentration 25 M), concentrated enzyme (100 mU) and mediator solution (Wnal concentration 1 mM).…”
Section: Screening Of Mediatorsmentioning
confidence: 99%
“…Usually, mediators are used with laccase in order to optimize the process. Once oxidized by the enzyme, these molecules act as electron scavenger and attack the dye, which eventually results in bleaching in the end [14,15].…”
Section: Introductionmentioning
confidence: 99%